Comparison of the Reverse-Remodeling Effect of Pharmacological Soluble Guanylate Cyclase Activation With Pressure Unloading in Pathological Myocardial Left Ventricular Hypertrophy - Ruppert, Mihály; Korkmaz-Icöz, Sevil; Li, Shiliang; Brlecic, Paige; Németh, Balázs Tamás; Oláh, Attila; Horváth, Eszter M.; Veres, Gábor; Pleger, Sven; Grabe, Niels; Merkely, Béla; Karck, Matthias; et al. (Frontiers in Physiology, 2019)
Background: Pressure unloading induces the regression of left ventricular myocardial hypertrophy (LVH). Recent findings indicate that pharmacological activation of the soluble guanylate cyclase (sGC) - cyclic guanosine monophosphate (cGMP) pathway may also exert reverse-remodeling properties in the myocardium. Therefore, we aimed to investigate the effects of the sGC activator cinaciguat in a rat model of LVH and compare it to the “gold standard” pressure unloading therapy. Methods: Abdominal aortic banding was performed for 6 or 12 weeks. Sham operated animals served as controls. Pressure unloading was induced by removing the aortic constriction after week 6. The animals were treated from week 7 to 12, with 10 mg/kg/day cinaciguat or with placebo p.o., respectively. Cardiac function and morphology were assessed by left ventricular pressure-volume analysis and echocardiography. Additionally, key markers of myocardial hypertrophy, fibrosis, nitro-oxidative stress, apoptosis and cGMP signaling were analyzed. Results: Pressure unloading effectively reversed LVH, decreased collagen accumulation and provided protection against oxidative stress and apoptosis. Regression of LVH was also associated with a full recovery of cardiac function. In contrast, chronic activation of the sGC enzyme by cinaciguat at sustained pressure overload only slightly influenced pre-established hypertrophy. However, it led to increased PKG activity and had a significant impact on interstitial fibrosis, nitro-oxidative stress and apoptosis. Amelioration of the pathological structural alterations prevented the deterioration of LV systolic function (contractility and EF) and improved myocardial stiffness. Conclusion: Our results indicate that both cinaciguat treatment and pressure unloading evoked anti-remodeling effects and improved LV function, however in a differing manners.